2013
DOI: 10.1371/journal.ppat.1003744
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus-Induced Cytoplasmic Organelles Use the Nuclear Transport Machinery to Establish an Environment Conducive to Virus Replication

Abstract: Hepatitis C virus (HCV) infection induces formation of a membranous web structure in the host cell cytoplasm where the viral genome replicates and virions assemble. The membranous web is thought to concentrate viral components and hide viral RNA from pattern recognition receptors. We have uncovered a role for nuclear pore complex proteins (Nups) and nuclear transport factors (NTFs) in the membranous web. We show that HCV infection leads to increased levels of cytoplasmic Nups that accumulate at sites enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 68 publications
14
86
1
Order By: Relevance
“…Accordingly, several HCV proteins, including Core, contain functional nuclear localization signal and nuclear export signal sequences that are required to bind cargo proteins and cross the NPC (17). This hypothesis would be in agreement with the model proposed by Neufeldt et al (16), which suggests the insertion of NPC in the cytoplasm of infected cells to compartmentalize virus replication/assembly. To date, viruses have been described to target the NPC, to cross the nuclear envelope, and/or to control host transcription.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, several HCV proteins, including Core, contain functional nuclear localization signal and nuclear export signal sequences that are required to bind cargo proteins and cross the NPC (17). This hypothesis would be in agreement with the model proposed by Neufeldt et al (16), which suggests the insertion of NPC in the cytoplasm of infected cells to compartmentalize virus replication/assembly. To date, viruses have been described to target the NPC, to cross the nuclear envelope, and/or to control host transcription.…”
Section: Discussionsupporting
confidence: 89%
“…5). A previous study identified Nup98 as an important host protein for HCV infection (16). Here, we show that Nup98 is copurified with extracellular HCV virions ( Table 2), physically interacts with Core ( Fig.…”
Section: Discussionsupporting
confidence: 65%
“…9,47,48 Therefore, the observed topological alteration or modification of these structures by HCV infection may be determinant at the onset of an efficient infection. Indeed, a fraction of the viral proteins localize to mitochondria-associated endoplasmic reticulum membranes, [37][38][39] and we have shown that mitochondria-associated endoplasmic reticulum membranes-resident host factors are determinant at the onset of HCV infection. 39 Thus, it is conceivable that mitochondria-associated endoplasmic reticulum membranes are preferential sites for the initial establishment of HCV replicase complexes as it has previously been proposed.…”
Section: Reversion Of Hcv-induced Ultrastructural Alterations By Dirementioning
confidence: 89%
“…Indeed, many proteomic and functional RNAi genetic screens revealed that modulation of nuclear pore complexes (NPCs), nuclear transport receptors and the RAN‐GTPase system have profound effects on viral replication . For instance, interactions between viral proteins, nucleoporins (Nups), RAN, importin‐α (IMP‐α), importin‐β (IMP‐β) and exportin (EXP) have been observed with hepatitis C virus (HCV), picornavirus, and human immuno‐deficiency virus (HIV)‐1 . In HCV infection, viral proteins (core, NS2, NS3 and NS5A) harbor a nuclear localization signal (NLS) and/or nuclear export signal (NES) suggesting that nuclear‐cytoplasmic shuttling is important for it virus life cycle that is mostly within the cytoplasm .…”
Section: Introductionmentioning
confidence: 99%